The Effect of Profitability, Leverage, Company Size, and Public Accounting Office Size on Audit Delay: an Investigation on IDX-Listed Manufacturing Companies - Maulina Tiar Rahmawati; Islahuddin; Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of profitability, leverage, firm size, and size of public accounting firm on audit delay in manufacturing companies on Indonesia Stock Exchange. This Study provide on explanation of lateness of audit report thus effect on inapproriate financial statement report to Indonesia Stock Exchange. The sample of this study is manufacturing companies listed on Indonesia Stock Exchange from 2016 to 2019 as many as 80 observations from 168 manufacturing companies in total. This study used multiple linear regression to analysed data. The type of data used in this research is secondary data. The paper conclude that there are companies have lateness in submitting audited financial statement to Indonesia Stock Exchange as resulted of audit delay. This study only examine manufacturing companies listed on Indonesia Stock Exchange thus the result of this paper could not used to represent all companies in Indonesia Stock Exchange. The novelty of this research occur on population characteristic and industry type used